Correlation between early perforation of cover screws and marginal bone loss: a retrospective study - Nele Van Assche, Bruno Collaert, (Blackwell Synergy, 2008)
Aim: This retrospective study aimed to determine the consequence of early cover screw exposure on peri-implant marginal bone level. Material and Methods: Sixty Astra Techs MicroThread implants installed in partially edentulous jaws were compared: 20 implants were placed following a two-stage procedure and were unintentionally exposed to the oral cavity (two-stage exposed), 20 implants were placed following a two-stage procedure and were surgically exposed after a subgingival healing time of 3–6 months (two-stage submerged), and 20 implants were placed following a one-stage surgical protocol (one-stage). Digital radiographs were taken at implant placement for all implants, and after abutment surgery for the two-stage exposed and two-stage submerged groups or after 3 months for the one-stage group. Bone loss mesially and distally was measured with an on-screen cursor after calibration. Results: Mean bone re-modelling was 1.96mm (range: 0.2–3.2 mm) around the two-stage exposed implants, 0.01mm (range: 0.0–0.3 mm) around the two-stage submerged implants and 0.14mm (range: 0.0–1.2 mm) around the one-stage implants. Conclusion: The unintentional perforation of two-stage implants resulted in significant bone destruction, probably because the biological width was not considered.